2021
DOI: 10.24083/apjhm.v16i2.659
|View full text |Cite
|
Sign up to set email alerts
|

Do Socio-Demographic and Corona Reassurance-Seeking Behaviour Predict Corona Anxiety? - A study among Indian population.

Abstract: Introduction: The COVID-19 pandemic has caused severe anxiety and affected mental and psychological health of the people. Virus related anxiety is thought to be affected by several socio-demographic factors, individual’s risk-perception, and personality. Objective: The objective of the study was to investigate the predictors of corona virus-related general anxiety and death anxiety during the COVID-19 outbreak in India. More specifically, the study examined the COVID-19 related reassurance-seeking behaviours, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was reported that 24% of dental students were assessed as having a severe degree of reassurance-seeking behavior. 7 Reassurance-seeking behaviors have been associated with viral anxiety, health anxiety, and death anxiety 8 among the Indian population and health worry or fear of illness and death 9 among the general population in Iraq. In this pandemic, an individual's viral anxiety can provoke reas-surance-seeking behaviors such as washing hands, checking body temperature, monitoring physical symptoms, or collecting information on COVID-19 by searching the internet.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 24% of dental students were assessed as having a severe degree of reassurance-seeking behavior. 7 Reassurance-seeking behaviors have been associated with viral anxiety, health anxiety, and death anxiety 8 among the Indian population and health worry or fear of illness and death 9 among the general population in Iraq. In this pandemic, an individual's viral anxiety can provoke reas-surance-seeking behaviors such as washing hands, checking body temperature, monitoring physical symptoms, or collecting information on COVID-19 by searching the internet.…”
Section: Introductionmentioning
confidence: 99%